Des pratiques pédagogiques de l’enseignement du lire/écrire, déclarées par des enseignantes du primaire - Rakia Laroui; Magalie Morel; Stéphanie Leblanc (Éducation et Socialisation)
Many elementary school students have difficulties in reading and writing. However, researches showed that effective teaching practices have positive impacts in the success of students at school precisely in their reading and writing learning process. This paper presents results of a study on reported reading and writing teaching practices conducted on four sixth grade teachers by following a literature review on social constructivist theories winning practices. The results showed that they use innovative practices that incorporate reading, writing and oral communication teachings in class ; even if they still have traditional practices such as dictation. They also focused on interdisciplinary and cross-functional projects. Those activities are more significant because of their closeness with the children’s reality and interests. In sum, the interviews revealed the teachers’ methods as a whole and an open-plan, which many effective practices studies recommend.